Tracing the consequences of child poverty : evidence from the young lives study of Ethiopia, India, Peru and Vietnam - Boyden, Jo; Dawes, Andrew; Dornan, Paul, 1978-; Tredoux, Colin (Policy Press, 2018)
This text draws on evidence on two cohorts of children, from 1 to 15 and from 8 to 22 growing up in Ethiopia, India, Peru and Vietnam over the past 15 years. It examines how poverty affects children's development in these countries, and how policy has been used to improve their lives.